Lateral Buckling of Glare for Aerospace Application - Eyüp Yeter; Burak Şahin (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Glare (Glass Reinforced Aluminium) which consists of fibre metal laminate composite consisting of aluminium and glass is used aerospace structures are supposed to buckling and impact loads. Lateral buckling analyses were made to determine critical buckling loads, and results were compared to Al 2024-T3 in this paper. Weight and load carrying capacity of Glare grades were taken into consideration and the importance of weight to critical load was stated. Numerical works were carried out by starting with Glass and Aluminum then continued for Glare Grades of Glare 2A, Glare 2B, Glare 3A, Glare 3B, Glare 4A, Glare 4B, Glare 5A, Glare 5B, Glare 6A and Glare 6B to estimate buckling load values. Several comparisons were presented for Glare grades based on Al 2024-T3 through paper. Glare 2A, 2B, 3A, 3B, 6A and 6B Grades have lower weight and buckling load values compared to Al 2024-T3. Lower weight is essential for aerospace applications. But optimum weight and load carrying capacity can be selected for intended applications by taking weight and load into consideration at same time. Although Glare grades of 4A 2-1, 4B 2-1, 5A 2-1 and 5B 2-1 having closer weight (17.60g, 17.60g, 19.13g and 19.13g respectively) to Al 2024-T3 (17.31g), higher buckling loads were determined for Glare grades numerically. The best choice for Glare as an alternative to Al 2024-T3 under lateral buckling loading can be decided for point of views of less weight to critical load ratio.